The neo-liberal state - Plant, Raymond (Oxford : Oxford University Press, 2010)
There is a world-wide debate at the moment about the appropriate role for the state in modern societies in the light of the world financial crisis. This text provides a comprehensive analysis and critique of neo-liberal or economic liberal ideas on this issue.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Neoliberalism; State, The